The Dynamics of Madrasah Diniyah Wustha Learning and Its Relevance to the Results of Islamic Religious Education Subject Achievement - Vivi Ravita; Ahmad Saefudin; Khasnah Khasnah (Research Journal on Teacher Professional Development, 2024)
This study aims to determine the dynamics of Madin Wustha's learning and its relevance to students' learning outcomes of Islamic Religious Education (PAI). The type of research is quantitative with a comparative approach. Data collection techniques utilize the documentation of PAI learning achievements, starting from daily tests, mid-semester tests, end-of-semester tests, and report cards. The sample of this study was all students of Class VIII at SMP Negeri 2 Kedung Jepara, totaling 57 students. Data analysis using t-test Independent sample test. The results showed that the PAI learning outcomes of students who took Madin Wustha were in the very good category with an average score of 88, while those who did not take it were in the good category with an average score of 79. The results of calculations using the t-test concluded that there were differences in PAI learning outcomes. between students who follow Madin Wustha and students who do not follow Madin Wustha. Suggestions that can be taken from this research are the schools, especially teachers, to further improve the quality of education, one of which is to understand the conditions and educational background of students. So that it can achieve maximum learning outcomes.